2019
DOI: 10.1016/j.jdermsci.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 activation in epidermal keratinocytes induces Langerhans cell activation to form an essential circuit for psoriasis via IL-23 production

Abstract: Background: Psoriasis is an inflammatory disease associated with aberrant crosstalk between the epidermis and immune system. However, the role of Langerhans cells (LCs) in psoriasis remains controversial. Objectives: To elucidate whether LCs are functionally involved in the development of psoriasis using a mouse model. Methods: Two lines of transgenic mice were used and crossed. They included K5.Stat3C, the psoriasismodel mouse and langerin DTR knock-in (KI) mouse. We performed immunofluorescence staining for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…However, the in vivo distinction of a rather DC-like state versus a macrophage-like state is nontrivial, and the role of Tip-DCs/macrophages is under debate [70,71]. Although a single prominent cell type might be responsible for a certain cytokine response in a specific disease state, the cytokine milieu is sustained by various contributors (e.g., Langerhans cells, inflammatory dendritic cells, and mast cells [72][73][74]).…”
Section: Psoriasismentioning
confidence: 99%
“…However, the in vivo distinction of a rather DC-like state versus a macrophage-like state is nontrivial, and the role of Tip-DCs/macrophages is under debate [70,71]. Although a single prominent cell type might be responsible for a certain cytokine response in a specific disease state, the cytokine milieu is sustained by various contributors (e.g., Langerhans cells, inflammatory dendritic cells, and mast cells [72][73][74]).…”
Section: Psoriasismentioning
confidence: 99%
“…Several studies exploiting the LC‐depleted mouse favor a contrasting outcome. Activation of the STAT3 pathway in keratinocytes and TLR in LC can induce LC to generate IL‐23, which is crucial in the pathogenesis of psoriasis . Mice with deletion of the p38α signal in LC produce much less IL‐23 and IL‐6, thereby reducing the psoriatic inflammation .…”
Section: Langerhans Cellsmentioning
confidence: 99%
“…84 In addition, studies have shown that the activation of Stat3 in keratinocytes may affect the activation of LCs at least partly through IL-1 α stimulation, and their existence is related to the occurrence or aggravation of psoriasis, called the Koebner phenomenon, which is caused by IL-23. 85,86 This activation leads to the intraepidermal circuit of KC-LCs and the activation of the IL-23/IL-17 axis, which leads to the occurrence and development of psoriasis. Human β-defensin 3 (HBD3) is a small antimicrobial peptide that has a chemotactic effect on immune cells and plays a small role in promoting the development of psoriasis by inducing the increase of IL-23 produced by epidermal LCs.…”
Section: Patients With Psoriasismentioning
confidence: 99%
“…In addition, studies have shown that the activation of Stat3 in keratinocytes may affect the activation of LCs at least partly through IL‐1 α stimulation, and their existence is related to the occurrence or aggravation of psoriasis, called the Koebner phenomenon, which is caused by IL‐23 85,86 . This activation leads to the intraepidermal circuit of KC‐LCs and the activation of the IL‐23/IL‐17 axis, which leads to the occurrence and development of psoriasis.…”
Section: The Role Of Langerhans Cells In Psoriasismentioning
confidence: 99%